Treatment of malignant ventricular arrhythmias with the automatic implantable cardioverter defibrillator. - Slater, A D (1989)
Twenty-eight patients with malignant ventricular arrhythmias were treated with the automatic implantable cardioverter-defibrillator (AICD) in a 14-month period. Thirteen patients were resuscitated from a ventricular fibrillation (VF) episode. Fifteen patients presented with ventricular tachycardia (VT) refractory to medical therapy. The etiology was coronary artery disease in 23 of 28 patients (82%), dilated cardiomyopathy in 2 of 28 patients (7%), sarcoidosis in 2 of 28 patients, and 1 patient in 28 had lupus erythmatosis. The mean left ventricular ejection fraction was 29%. A total of 27 of 28 patients (96%) patients had inducible ventricular tachycardia using programmed stimulation. The patients considered for AICD implant failed a mean of 3.6 antiarrhythmic drugs. Rate counting and defibrillating leads were inserted through a lateral thoracotomy in 17 patients and a mediansternotomy incision in 11 patients in conjunction with another cardiac procedure in 10 patients. The generators were positioned in a subcutaneous pocket beneath the left costal margin. There were no operative deaths. The mean follow-up was 6.7 months (range 1 to 14) with no VT/VF deaths in patients with defibrillators. The study demonstrated that AICD is an effective device for prevention of sudden cardiac death.